Myrrh Oil Reduces Gingival Inflammation and Inhibits Gram Negative Dental Plaque Bacteria at Early Stages – A Randomized Control Trial - Bhagyashree Lenka; Rinkee Mohanty; Anurag Satpathy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim: To assess the anti-plaque, anti-inflammatory and antimicrobial efficacy of Myrrh oil as an adjunctto scaling and root planing in the treatment of gingival inflammation. Materials and Methods: Subjectswith moderate to severe gingivitis were recruited for this parallel arm, double blind randomized controlledtrial. All subjects underwent SRP at baseline and were randomly divided into Group A (placebo control)and Group B (Myrrh oil). Plaque index (PI), gingival index (GI) and microbiological analysis was carriedout at baseline, 48 hrs and 1week interval Results: Thirty subjects completed the study. Myrrh oil showedanti-inflammatory and antibacterial efficacy. There were no statistically significant differences betweenthe groups with respect to plaque score at baseline (p=0.25), after 48 hours (p=0.16) and after 1 week(p=0.37). There was a significantly lower gingival inflammation (p=0.02) recorded in the Myrrh oil groupafter 48 hrs. A greater reduction in inflammation from baseline at 48hrs was observed, although there wasno statistically significant difference in gingival inflammation between the groups after1 week (p=0.39).A significantly greater number of fields were observed with score 1 and lesser number of fields with 2 forgram +ve (p<0.001) and gram –ve (p=0.002) bacteria in Myrrh Oil group indicating overall lesser gram+ve and Gram –ve bacterial count in comparison to commercially available Myrrh oil. No adverse effectswere reported by any subject. Conclusion: Myrrh oil when used as an adjunct with scaling and root planningsignificantly reduced the gingival inflammation in 48 hrs and gram-ve bacteria after 1 week.